1978
DOI: 10.1128/aac.14.3.498
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of Clindamycin into Decubitus Ulcers

Abstract: Forty tissue samples, primarily of skin and bone, were obtained from 29 patients undergoing excision of decubitus ulcers after intravenous injection of 600 mg of clindamycin. Antibiotic concentrations exceeded 2.5 μg/g in 80% of the samples. In 50% of the instances, tissue levels were greater than those simultaneously present in the serum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Lower concentrations were measured in bone , skin , and adipose tissues [ 129 ], but they were higher than the MIC values of the most common pathogens. On the contrary, in 29 subjects with decubitus ulcers, the tissue/plasma ratios were 1X for both bone and skin 0.5–1.5 h after dosing [ 130 ]. In lower limb ischemia, the different rates of perfusion influenced the penetration of clindamycin 0.6 g q8h in muscle (0.4–0.5X), bone (0.2–0.3X), and skin (0.2–0.4X) [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lower concentrations were measured in bone , skin , and adipose tissues [ 129 ], but they were higher than the MIC values of the most common pathogens. On the contrary, in 29 subjects with decubitus ulcers, the tissue/plasma ratios were 1X for both bone and skin 0.5–1.5 h after dosing [ 130 ]. In lower limb ischemia, the different rates of perfusion influenced the penetration of clindamycin 0.6 g q8h in muscle (0.4–0.5X), bone (0.2–0.3X), and skin (0.2–0.4X) [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…In these patients, the additional presence of diabetes had no effect on the penetration of ceftazidime into the bone [67]. Yet another study found that bone levels of clindamycin often exceeded serum concentrations following a single 600-mg dose given before excision of a decubitus ulcer [68]. Fosfomycin, with activity against MRSA and Staphylococcus aureus, including both MSSA and MRSA, has, been shown to penetrate adequately into bone in DFI using the microdialysis technique [69].…”
Section: Osteomyelitis: Antibiotic Pharmacokinetic and Pharmacodynamimentioning
confidence: 99%